Associação entre a concentração de selênio, o polimorfismo Pro198Leu da glutationa peroxidase 1 e a mortalidade em pacientes com choque séptico - Costa, Nara Aline [UNESP] (2014)
The oxidative stress is recognized as a key feature of septic shock. In addition, in patients with systemic inflammatory response, plasma selenium concentration falls independently of selenium status. However, the pathophysiologic role of selenium concentration in patients with septic shock remains unknown. Therefore, the objective of this study was to evaluate the association of erythrocyte and plasma selenium concentration with glutathione peroxidase (GPx1) activity, GPx1 polymorphisms and with intensive care unit (ICU) and hospital mortality in septic shock patients. This is an prospective, observational clinical study held in three intensive care units in a university hospital. A total of 110 consecutive patients older than 18 y (57,6 ± 15,9 y; 63,6% males) with septic shock on admission or septic shock during their ICU stay who were admitted to the ICU between January and August 2012 were evaluated. At the time of the patients’ enrollment, demographic information was recorded. Blood samples were taken within the first 72 h of the patient’s admission or within 72 h of the septic shock diagnosis for determination of selenium status, protein carbonyl concentration, GPx1 activity and GPx1 Pro198Leu polymorphism genotyping. Regarding selenium status, only erythrocyte selenium concentration was lower in septic patients who died in ICU and hospital. The genotype frequencies for GPx1 Pro198Leu polymorphism were 55%, 38% and 7% for Pro/Pro, Pro/Leu and Leu/Leu, respectively. GPx1 activity was different between groups and was higher in the Leu/Leu genotype. In the Cox regression models, erythrocyte selenium concentration was associated with ICU (HR:0.965; 95%CI:0.943-0.988; p: 0.002) and hospital mortality (HR: 0.968; 95%CI: 0.948-0.989; p: 0.003) in patients with septic shock even after adjustment for age, gender and APACHE II. Erythrocyte selenium concentration was a predictor of ICU and hospital mortality in patients with septic ...